Tanggung Jawab Sosial Perusahaan dan Akses Pendanaan - Wendy Tandiawan (Penerbit Goodwood, 2022)
Purpose: Purpose of this research is to find out the effect of Corporate Social Responsibility (CSR) on cost of equity and capital constraint, as well as the effect of the cost of equity itself to capital constraint. Moreover, this research attempts to see the relationship effect of the exogenous variable towards the endogenous variable, and to test the position of cost of equity variable as an intervener. Methodology/approach: Type of this research is descriptive and verification, where the focus is to find the effect and amount of the effect itself between the exogenous and endogenous variable. In case of the cost of equity as an intervening variable, multiple linear regression with Two Stage Least Squareis used. The sampling method for this research is a purposive sampling. To see the effect between the variables, t-test and F-test are used. Subjects of this research are the listed manufacturing companies in Indonesia Stock Exchange, and the objects are Corporate Social Responsibility as the exogenous variable that consist of stakeholder engagement and CSR Disclosure as proxy, and cost of equity as the endogenous variable, as well as the capital constraint. Results/findings: The research result proves that the first structural model to see the effect of CSR on cost of equity partially or simultaneously is not significant. As the opposite, the second model to test the effect of CSR on capital constraint has significant relationship partially and simultaneously. Nevertheless, cost of equity is not proven to be an intervening variable for CSR and capital constraint.